Understanding Indonesia’s Generation Z - Dwidienawati, Diena; Gandasari, Dyah (International Journal of Engineering and Technology, 2018)
It seems like researchers have just started to finally understand Generation Y (Gen Y). Now, along comes Generation Z (Gen Z). What difference can a decade make? Different social and economic conditions shaped different generations with different values, behaviours, and attitudes. A study in the USA confirms that Gen Z is more realistic and self-reliant. Global events and developments will impact different countries at different rates and intensities. Therefore, generational characteristics may be cultural- and country- specific. This study aimed to see the characteristics of Gen Z in Indonesia. A descriptive quantitative study was conducted at one prominent private university in Jakarta, Indonesia. Eighty-nine survey respondents answered a questionnaire with a voting pad. The finding of the study confirms that unlike Gen Y, Gen Z in Indonesia also considers job security and money important. Unlike Gen Y, they are willing to work harder for higher pay and relocate to other cities and countries for decent job opportunities. They also consider face to face communication important. Due to small size samples, a bigger sample size is recommended for the generalization of Gen Z characteristics in Indonesia. The theoretical contribution of this study is adding empirical evidence of Gen Z characteristics. Practically, this study will give insight to management that Gen Z is different than Gen Y; therefore, they need different treatment.Â Â